METHODS OF DEVELOPING TECHNICAL TRAINING OF YOUNG FOOTBALL PLAYERS - Ataniyazov , Bekzod Ilxomovich (Educational Research in Universal Sciences, 2023)
In the article, on the topic of methods of developing the technical training of young players, the development of technical training of players in the sports sections of general secondary schools and academic lyceums is raised as an urgent problem. it was developed and the issues that this problem is relevant today are shown.